2012
DOI: 10.1148/radiol.12112470
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose Reduction at Multidetector CT with Adaptive Statistical Iterative Reconstruction for Evaluation of Urolithiasis: How Low Can We Go?

Abstract: Image quality improvements with ASIR at reduced radiation dose of 1.8 mGy enabled effective evaluation of urinary calculi without substantially affecting diagnostic confidence. © RSNA, 2012.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 32 publications
8
66
0
4
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The researchers primarily evaluated the possibility of reducing the dose by increasing the pitch, 8 lowering the tube current, 9-11 using automatic tube current modulation, 12 reducing the tube voltage 13,14 and using iterative reconstruction algorithms. [13][14][15][16][17][18][19] Another simple and effective way to reduce the dose is to limit acquisition coverage from the top of the kidneys to the lower edge of the bladder. For the lower acquisition limit, the lower edge of the symphysis pubis bone is an accurate landmark.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The researchers primarily evaluated the possibility of reducing the dose by increasing the pitch, 8 lowering the tube current, 9-11 using automatic tube current modulation, 12 reducing the tube voltage 13,14 and using iterative reconstruction algorithms. [13][14][15][16][17][18][19] Another simple and effective way to reduce the dose is to limit acquisition coverage from the top of the kidneys to the lower edge of the bladder. For the lower acquisition limit, the lower edge of the symphysis pubis bone is an accurate landmark.…”
Section: Introductionmentioning
confidence: 99%
“…The strategy of this study was to reduce the estimated radiation dose during the craniocervical CTA and have better image quality by using iDose 4 in image reconstruction compared to FBP CT. Thus we conclude that HIR algorithm not only improves the image quality but also helps to reduce the radiation dose.…”
Section: Discussionmentioning
confidence: 99%
“…4 th generation iterative reconstruction technique is better in preventing photon starvation artifacts (streaks, bias) prior to image creation and in maintaining image texture. iDose…”
Section: Th Generation Iterative Reconstruction Technique Also Calledmentioning
confidence: 99%
See 1 more Smart Citation
“…Kilkarni et al have shown that you can reduce the mean radiation dose for the evaluation of urolithiasis down to 1.8 mSv without compromising diagnostic accuracy, and for patients weighing less than 200 pounds the dose can be as low as 1.3 mSv which is a radiation dose similar to a 2 shot film of the kidneys, ureters and bladder. 9 My opponents will say that sure this is all well and good but most centers are not performing low dose CT. I counter simply with the question "why not?…”
Section: Conmentioning
confidence: 99%